POLA KEMITRAAN PROGRAM PRAKTEK KERJA INDUSTRI (PRAKERIN) DI SMKN 7 BONE - Ayu Lestari Abbas; Ansar; Muhammad Ardiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the gap between the skills possessed by graduates of Vocational High Schools (SMK) and the skills required by the workforce and industry. The study aims to: (1) describe the partnership patterns of the Industrial Work Practice (Prakerin) program at SMKN 7 Bone; (2) identify supporting and inhibiting factors in these partnership patterns; and (3) determine strategies to strengthen the partnership between SMKN 7 Bone and the business and industrial sectors (DuDi). A qualitative research method was employed, with data collected through interviews, observations, and documentation. Data analysis involved three processes: data reduction, data presentation, and verification, with data validity checked using source and method triangulation techniques. The results of the study indicate that the description of the internship partnership pattern between SMKN 7 Bone and the Business World and Industry World is four, namely the signing of the MoU between the school and the Business World and Industry World (DuDi), determining the internship schedule, adjusting the school curriculum and the needs of the Business World and Industry World (DuDi) and Supervision and evaluation of student performance during internship. Supporting factors include competency suitability, effective communication, joint commitment, regulatory support and adequate resources. While the inhibiting factors are lack of understanding of the industry, industry limitations, student readiness, poor communication and unstructured evaluation. While strengthening strategies can be carried out through increased communication, involvement of the Business World and Industry World in the curriculum, student training, monitoring and evaluation, partnership forums and promotion of success.